Durability performance of nano-SiO2 modified OPC-SAC composites subjected to sulfuric acid attack. (31st March 2023) - Cao, Runzhuo; Yang, Junfen; Li, Guoxin; Zhou, Qun; Niu, Mengdie
Highlights: Resistance, hydration and microstructure of mortars with nano-SiO2 under sulfuric acid were studied. Composites with nano-SiO2 reduced degradation kinetics loss. Nano-SiO2 induced chemical and microstructure optimization can reduce the degradation caused by acid. Abstract: Exposure of cement-based structures to sulfuric acid environments can cause significant degradation. Therefore, this study focuses on the effect of nano-SiO2 on the sulfuric acid resistance of ordinary Portland cement (OPC)-sulfoaluminate cement (SAC) composites (as repair material). Samples were exposed to three concentrations of acid solution. The degradation kinetics, chemistry, and microstructures of the composites were analyzed. The results of degradation kinetics (dimensional change, mass and strength loss) showed that the nano-SiO2 modified composites had a lower degradation rate compared to the composites without nano-SiO2 . XRD, TG, MIP and SEM analyses demonstrate that nano-SiO2 promoted hydration and improved structural compactness, which can not only enhance the diffusion resistance of composites to H + and SO4 2-, but also form a protective barrier in acid environments. However, diffusion–dissolution-precipitation is still the main mode of degradation in composites subjected to sulfuric acid attack, regardless of nano-SiO2 content mixed into the composite system.